The Independent State Legislature Theory – the Underlying Ideas and the Threats - Paweł Króliczek (Krytyka Prawa, 2023)
This article discusses the independent state legislature theory, which has been the subject of interest of an ever-growing group of American constitutionalists in recent years. This theory deals primarily with state legislatures’ power – derived directly from the US Constitution – to regulate federal elections. According to its underlying premises, this fact results in the absence of any tools to control the law enacted in this area as to its compliance with a given state’s constitution. Neither the electoral administration nor the state courts can interfere with these laws. They would therefore be subject to federal courts’ review only. However, the Supreme Court, in applying the political questions doctrine, has excluded many election law matters – other than those concerning funding – from its jurisdiction. As a result, such an important part of state law – one concerning fundamental political rights – would remain without any supervision inherent in modern democracies